Patient’s right to information – legal, medical and psychological aspects - Podciechowski, Lech; Królikowska, Anna; Hładuńska, Joanna; Wilczyński, Jan (Menopause Review/Przegląd Menopauzalny, 2009)
Patient’s right, who is treated in hospital or outpatient clinic to receive information is his inalienable right, entrenched in legislation. Effective delivery of information isn’t easy, especially when we have to communicate unfavourable or unexpected informations. Informed consent to treatment, including surgical procedures has legal force only if the information communicated to the patient is given in an approprative way. Our article brings the legal issues of information given to the patient from the perspective of legal-medical and psychological aspects of effective information to patients about their health condition.